Daily discharges modelling in a basin in southern Ecuador with precipitation and temperature estimated by satellite - Balcázar, L. (2019)
In some regions of the world, like southern Ecuador, meteorological data are scarce or do not exist. However, the data from products estimated by satellite are an alternative in these places and, in remote areas, can be the sole source of information available. This study evaluated the precipitation products CMORPH, PERSIANN-CDR and TRMM-3B42, and ERA-Interim temperature on the basin of the Catamayo River, located in southern Ecuador. CMORPH overestimates in average 50 % of the precipitation observed, while PERSIANN-CDR and TRMM-3B42 underestimate in average 20 and 10 %. Thus, the bias of the precipitation products was corrected with rain gauges. The CEQUEAU model was calibrated with the observed and estimated data (original and corrected) at 0.25°/~27 km of spatial resolution with the objective of modelling the daily discharges of the Catamayo River at Vicin station. The efficiency of the modelling was quantified with the following mathematical criteria: Nash-Sutcliffe efficiency coefficient (NSE), BIAS percentage (PBIAS) and coefficient of determination (r2). The results according to the NSE criterion, in the periods of calibration and validation, were 0.80 and 0.75 with the observed data, and with the satellite data (original): TRMM-3B42, 0.84 and 0.79, PERSIANN-CDR, 0.80 and 0.65, and CMORPH, 0.59 and 0.39. Correction of the bias of the estimated rainfall was positive when modelling with the CMORPH product and quite low with PERSIANN-CDR and TRMM-3B42. This study reveals the advantage of using satellite products to simulate the discharges in ungauged basins, in addition to using these data in their original spatial scale on the distributed hydrological models.